Pengaruh kepemimpinan dan kompensasi finansial terhadap kinerja karyawan PT Sinar Indah Perkasa Surabaya - Karmanto, Karmanto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
This study aims to examine and analyze the influence of leadership and financial compensation on employee performance. The analysis unit in this study was all employees as many as 54 people. Samples used a saturated sampling technique where members of the population were used as samples. Data analysis was performed using statistics with SPSS tools. F test results F value calculated 47.702 > F table and significance level 0.000 <alpha 0.05 means that simultaneously the variables of leadership and financial compensation have a significant effect on employee performance variables. Results of calculations with regression analysis multiple linear on t-test obtained coefficient value of 0.544 for leadership and 0.467 for financial compensation. The result is that partial leadership and financial compensation have a significant influence on employee performance.